(untitled) (Medico Legal Update, 2020)
Prepared two concentration of four new enriched media for isolation of some pathogenic bacteria including Acinetobacter baumannii, Klebsiella pneumoniae, Escherichia coli, and Serratia marcescens and identification of Serratiamarcescens that produce red pigment (prodigiosin) . The first concentration 12.5 g/l of plant extracte showed heavy growth of pathogenic bacteria on the four media . The second concentration 25 g/l showed also growth of the pathogenic bacteria incubation in 37°C for 24h except on the Elettaria cardemomum agar and, Fenugreek (Trigonella foenum-graecum) seeds agar. Serratia marcescens produce red pigment on all the new media in both concentration . All isolates produce protease enzyme on Linum usitatissium seed agar . The result is a synthesis enrichment and inexpensive medium for different species of bacteria like Linumusitatissium enriched with a different materials and salt as amineral that suitable for growth organism without any morphological change of metabolisms feature, also identification Serratia marcescens by produce red pigment that important in medical with a wide range of biological activities.